Comparison of genotypic and phenotypic method for detection of Enterotoxigenic Escheichia coli isolated from diarrheal patients - Alam, Farzana (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2010